A treatise on money : volume 1, the pure theory of money - Keynes, John Maynard (London : Macmillan & Co Ltd., 1930)
The book examines monetary factors, the rate of investment and their fluctuations. It also considers the management and international management of money and problems associated with them.
"Comes in two volumes".
Includes bibliographical references.
lje 24/01/2019
Loans
Keywords: Money; Banks and banking